Effectiveness Of Digital Flipbook Media On Buttercream Material In Improving Students’ Knowledge In A Cake Decoration Course - Seruni Nitihani; Guspri Devi Artanti; Cucu Cahyana (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study examined the effectiveness of a digital flipbook on buttercream material in improving students’ knowledge in a university Cake Decoration course. A quantitative pre-experimental approach with a one-group pre-test–post-test design was employed. The participants were 70 applied-undergraduate culinary students selected through purposive sampling. The learning medium was a 72-page Heyzine-based flipbook combining text, photographs, process diagrams, navigation features, and embedded video tutorials. Knowledge was measured using 16 valid multiple-choice items derived from an initial pool of 30 questions. Instrument testing produced a reliability coefficient of 0.91. The data were analyzed using descriptive statistics, the Lilliefors normality test, the Wilcoxon signed-rank test, and average normalized gain. Mean scores increased from 74.375 (SD = 17.650) on the pre-test to 86.071 (SD = 7.832) on the post-test. Because both distributions were non-normal, the Wilcoxon test was applied and indicated a significant difference (W = 357; Z = −4.227; p < .001). The average N-Gain was 0.456, which falls within the moderate category. These findings show that the digital flipbook effectively improved students’ knowledge while also reducing score dispersion. The medium is therefore suitable as a flexible, multimodal learning resource for theory and procedure-oriented culinary instruction